2016
DOI: 10.1371/journal.pone.0162046
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Novel Host Jack Pine Do Not Prevent Host Acceptance and Colonization by the Invasive Mountain Pine Beetle and Its Symbiotic Fungus

Abstract: Fatty acids are major components of plant lipids and can affect growth and development of insect herbivores. Despite a large literature examining the roles of fatty acids in conifers, relatively few studies have tested the effects of fatty acids on insect herbivores and their microbial symbionts. Particularly, whether fatty acids can affect the suitability of conifers for insect herbivores has never been studied before. Thus, we evaluated if composition of fatty acids impede or facilitate colonization of jack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Among terpenes, monoterpenes are the most studied because of their importance to MPB behavior (Erbilgin et al ., ) and to host resistance (Boone et al ., ; Erbilgin et al ., ). Conifers also contain other classes of compounds, such as fatty acids, that can be toxic to MPB (Ishangulyyeva et al ., ).…”
Section: Approach Undertakenmentioning
confidence: 97%
See 3 more Smart Citations
“…Among terpenes, monoterpenes are the most studied because of their importance to MPB behavior (Erbilgin et al ., ) and to host resistance (Boone et al ., ; Erbilgin et al ., ). Conifers also contain other classes of compounds, such as fatty acids, that can be toxic to MPB (Ishangulyyeva et al ., ).…”
Section: Approach Undertakenmentioning
confidence: 97%
“…Recently, Ishangulyyeva et al . () have shown that G. clavigera grows similarly in media amended with fatty acids at concentrations present in jack or lodgepole pine phloem. Furthermore, samplings of different jack and lodgepole pine populations in various places in western Canada indicated that the composition of fatty acids was similar between the two species, suggesting that the composition of jack pine fatty acids is compatible with MPB and its fungal symbionts.…”
Section: Approach Undertakenmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty acids are major components of plant lipids, can affect growth and development of insect herbivores and influence host suitability to invasive insects [43]. Additionally, the insecticidal and antifeedant action of fatty acids and esters has been described.…”
Section: Growthmentioning
confidence: 99%